Civil Relationship of Children Born without Marriage with Biological Father based on Constitutional Court Decision Number 46/PUU-VIII/2010 - Cok Gede Mega Putra (Warmadewa Press, 2020)
The purpose of this study is to analyze the civil relationship between the children born without marriage with his biological father and the arrangement about the civil relationship between the children whose mothers did not have marriage. This study is a normative juridical which is the approach used in this is is the statute approach, the case approach, and the conceptual approach. The legal material comes from document studies. This study is analyzed qualitatively. The results of this study showed that the children born outside marriage initially have only a civil relationship with their mother and mother's family according to Article 43 of Law Number 1 of 1974 concerning Marriage on what is meant by a child outside of marriage but with the Constitutional Court Decision Number 46/PUU-VIII/ 2010, then a child born outside marriage can have a civil relationship with father and his father's family. The father and mother have rights and obligations to the born, even if the child is born outside of marriage. In this study, it can be concluded that children born without marriage have civil relations with their biological father as stipulated in Decision of the Constitutional Court Number 46 / PUU-VIII / 2010. The arrangement of civic relationships between children whose mothers are not married as in Law Number 1 of 1974 on Marriage, but by Decision of the Constitutional Court Number 46/PUU-VIII/2010, the child has a civil relationship with his mother and father.